2022
DOI: 10.1371/journal.pone.0272946
|View full text |Cite
|
Sign up to set email alerts
|

Study on air temperature estimation and its influencing factors in a complex mountainous area

Abstract: Near-surface air temperature (Ta) is an important parameter in agricultural production and climate change. Satellite remote sensing data provide an effective way to estimate regional-scale air temperature. Therefore, taking Gansu section of the upper Weihe River Basin as the study area, using the filtered reconstructed high-quality long-time series normalized difference vegetation index (NDVI), interpolated reconstructed land surface temperature (LST), surface albedo, and digital elevation model (DEM) as the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In previous studies, LST and NDVI were two important parameters for Ta estimation [47,62]. In this study, NDVI significantly influenced long-term Ta modeling, with a maximum relative importance of 25% in the GLASS combination.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In previous studies, LST and NDVI were two important parameters for Ta estimation [47,62]. In this study, NDVI significantly influenced long-term Ta modeling, with a maximum relative importance of 25% in the GLASS combination.…”
Section: Discussionmentioning
confidence: 54%
“…The potential of the artificial neural network (ANN) model for temperature estimation has also been demonstrated [39,[43][44][45][46]. Runke et al applied the ANN model to achieve high-temperature estimation accuracy in complex mountainous areas [47]. Şahin utilized the ANN model to model monthly average temperatures for 20 cities [48].…”
Section: Introductionmentioning
confidence: 99%
“…This limitation becomes evident in areas with significant variations in elevation and ground cover types, resulting in imprecise temperature predictions. 44 Moreover, conventional image-level regression analyses, considered spatial methods, overlook critical factors affecting temperature variation. 45 These include latitude, longitude, altitude, topography, and the type of underlying surface, with altitude and topography exerting the most pronounced impact on LST.…”
Section: Introductionmentioning
confidence: 99%
“…While spatial interpolation is relatively straightforward and offers significant practical value, 43 it was observed that IMA largely relies on image time-dependence for data imputation. This limitation becomes evident in areas with significant variations in elevation and ground cover types, resulting in imprecise temperature predictions 44 . Moreover, conventional image-level regression analyses, considered spatial methods, overlook critical factors affecting temperature variation 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Some satellite images with high temporal resolution and equipped with thermal infrared bands are Sentinel-3 satellite images and Terra Moderate Resolution Imaging Spectroradiometer (MODIS) satellites. In observing air temperature using remote sensing technology, the first element that can be identified is surface temperature, therefore the surface temperature obtained by remote sensing systems needs to be converted back into air temperature based on satellite imagery [4]. The results of air temperature observations on each satellite have different levels of accuracy, sothe study of the comparison of Sentinel-3 and Terra MODIS satellite images for air temperature observations needs to be studied.…”
Section: Introductionmentioning
confidence: 99%